The behavior of maize hybrids generated from contrasting progenies regarding the use of nitrogen - Fernando Lisboa Guedes; Edivaldo José Ferreira Junior; Carlos Eduardo Caixeta de Castro; Carlos Henrique Pereira; Paulo Eduardo Rodrigues Prado; João Cândido de Souza (Acta Scientiarum. Agronomy, 2014)
The purpose of this study was to evaluate the performance of maize hybrids synthesized from contrasting genotypes with regard to the use of nitrogen that were selected for their performance in topcrosses. Sixty-seven S0:1 progenies derived from the germplasm bank of Ufla were evaluated in topcross combinations with two testers  at two nitrogen levels. The six progenies with the greatest tolerance and responsiveness to nitrogen (RT) and the five with the least tolerance and responsiveness (RnTn) were selected and, were, afterwards, crossed in a complete diallel, for a total of 55 hybrid combinations. The following genetic parameters were estimated: genetic variance among the hybrids (σ^2G), broad sense heritability in the mean of the hybrids, and selective accuracy (r^2gg). It was observed that the genetic parameters were greater in the environments with available nitrogen and that the early selection by performance in topcrosses of progenies tolerant to low N levels may not be made with high intensity. The hybrids tolerant to low N levels were obtained by crossing contrasting parents.